The role of physical activity on cardiovascular risk factors in adolescents - Nadia Dwi Insani; Sukman Tulus Putra; Agus Firmansyah (Indonesian Pediatric Society, 2010)
Background Cardiovascular diseases remain the leading cause of death worldwide. Atherosclerotic process increases rapidly during adolescence. Physical activity is considered important in this period to modify cardiovascular risk factors, thus preventing disease in the future.Objective To determine whether different physical activity status in adolescence can influence body mass index (BMBMI), waist-to-hip ratio, blood pressure (BP), and blood lipid profile.Methods This was a cross-sectional descriptive study, conducted from December 2009 to January 2010. Adolescents who fulfilled the study criteria were classified into high and low physical activity category. Further examination including body mass index, waist-to-hip ratio, blood pressure, and blood lipid profile were performed.Results Adolescents with high physical activity had higher, but statistically insignificant, BMBMI compared to adolescents in the P=0.493] and significantly lower waist-to-hip ratio [0.80 (range 0.73-0.9) vs.. 0.82 (range 0.7-0.9), P=0.019]. Difference in BP was not statistically significant between both groups [diastolic BP (70 (range 60-90) mmHg vs. 70 (range 60-90) mmHg, P=0.148; systolic BP 100 (range 90-130) mmHg vs. 100 (range 90-140) mmHg, P=0.228)]. Blood lipid examination in the high activity group showed significantly higher HDL cholesterol and lower triglyceride compared to the low activity group [HDL 59.8 (SD 11.8) mg/dL vs. 54.7 (SD 8.9) mg/dL; p=0.044; triglyceride: 60 (range 32-203) mmHg vs. 82 (range 37-198) mmHg, P=0.014]. Total and LDL cholesterol [total cholesterol 169.8 (SD 28.6) mmHg vs. 181.2 (SD 30.8) mmHg, P=0.107; LDL 103.6 (SD 26.8) mmHg vs. 114.1 (SD 27.3) mmHg, P=0.100] were lower in the high activity group but not statistically different in both groups.Conclusions Adolescents with high physical activity show less cardiovascular risk factors compared to those in the low physical activity group.